Patient-reported outcomes in adults with congenital heart disease: Inter-country variation, standard of living and healthcare system factors. (15th January 2018) - Moons, Philip; Kovacs, Adrienne H.; Luyckx, Koen; Thomet, Corina; Budts, Werner; Enomoto, Junko; Sluman, Maayke A.; Yang, Hsiao-Ling; Jackson, Jamie L.; Khairy, Paul; Cook, Stephen C.; Subramanyan, Raghavan; et al.
Abstract: Aims: Geographical differences in patient-reported outcomes (PROs) of adults with congenital heart disease (ConHD) have been observed, but are poorly understood. We aimed to: (1) investigate inter-country variation in PROs in adults with ConHD; (2) identify patient-related predictors of PROs; and (3) explore standard of living and healthcare system characteristics as predictors of PROs. Methods and results: Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease – International Study (APPROACH-IS) was a cross-sectional, observational study, in which 4028 patients from 15 countries in 5 continents were enrolled. Self-report questionnaires were administered: patient-reported health (12-item Short Form Health Survey; EuroQOL-5D Visual Analog Scale); psychological functioning (Hospital Anxiety and Depression Scale); health behaviors (Health Behavior Scale–Congenital Heart Disease) and quality of life (Linear Analog Scale for quality of life; Satisfaction With Life Scale). A composite PRO score was calculated. Standard of living was expressed as Gross Domestic Product per capita and Human Development Index. Healthcare systems were operationalized as the total health expenditure per capita and the overall health system performance. Substantial inter-country variation in PROs was observed, with Switzerland having the highest composite PRO score (81.0) and India the lowest (71.3). Functional class, age, and unemployment status were patient-related factors that independently and consistently predicted PROs. Standard of living and healthcare system characteristics predicted PROs above and beyond patient characteristics. Conclusions: This international collaboration allowed us to determine that PROs in ConHD vary as a function of patient-related factors as well as the countries in which patients live.